Potential of Intercropping System in Sustaining Crop Productivity - Maitra, Sagar (International journal of agriculture environment & biotechnology, 2019)
Intercropping, an age old agricultural practice of cultivating two or more crops in the same space at the same time is generally adopted for more production by utilizing available growth resources. Choice of crops is very important to reap a better harvest from intercropping. The selection of a suitable intercropping system is sort of complicated issue as the success of intercropping depends much on the interactions between the component crop species, proper management practices and favorable environmental conditions. Intercropping has a huge potential and multiple advantages. The advantages are like efficient utilization of resources, enhancement of soil fertility by including legumes as component in mixture and soil conservation through covering the greater ground cover. Moreover, intercropping reduces attack of insect pest, checks the incidence of diseases and restricts weed population and thus minimizes the use of protection plant chemicals. This article addresses an overall view with a focus on prime advantages supported by evidences from the literature based on earlier research.